2019
DOI: 10.1111/ajps.12501
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Less Is More: Censorship, News Falsification, and Disapproval in 1989 East Germany

Abstract: Does more media censorship imply more regime stability? We argue that censorship may cause mass disapproval for censoring regimes. In particular, we expect that censorship backfires when citizens can falsify media content through alternative sources of information. We empirically test our theoretical argument in an autocratic regime—the German Democratic Republic (GDR). Results demonstrate how exposed state censorship on the country's emigration crisis fueled outrage in the weeks before the 1989 revolution. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…I also shed light on another puzzle in the literature on autocracies: why non-democratic regimes allow independent media, which may undermine the plausibility of propaganda (Gläßel and Paula 2020). Previous work has argued that such media can provide autocrats with useful information (Egorov, Guriev, and Sonin 2009;Lorentzen 2014) or make citizens more content (Kern and Hainmueller 2009;Huang and Yeh 2017).…”
mentioning
confidence: 86%
“…I also shed light on another puzzle in the literature on autocracies: why non-democratic regimes allow independent media, which may undermine the plausibility of propaganda (Gläßel and Paula 2020). Previous work has argued that such media can provide autocrats with useful information (Egorov, Guriev, and Sonin 2009;Lorentzen 2014) or make citizens more content (Kern and Hainmueller 2009;Huang and Yeh 2017).…”
mentioning
confidence: 86%
“…In many authoritarian countries, traditional and online media limit access to information (16)(17)(18)(19). While this control is imperfect, studies have shown that media control in autocracies has large effects on the opinions of the general public and the resilience of authoritarian regimes (20)(21)(22)(23)(24)(25)(26), even though there are moments when it can backfire (9,(27)(28)(29)(30)(31)(32). Evidence from China suggests that media control may be effective in part because individuals generally do not expend significant energy to find censored or alternative sources of information.…”
Section: Crisis Is a Gateway To Censored Informationmentioning
confidence: 99%
“…Physical surveillance includes numerous techniques: the following and monitoring of targets, opening correspondence, eavesdropping, and use of informants. Therefore, surveillance constitutes a distinct form of state repression compared with alternative nonviolent forms of repression such as detentions (Truex 2019), censorship (Gläßel and Paula 2019), or internet restrictions (Gohdes 2020).…”
Section: Surveillance and Resistancementioning
confidence: 99%
“…The dearth of evidence is surprising, given that physical surveillance constitutes one of the most consistently used measures of repression (Shelley 1996). Particularly in the former Eastern Bloc, regimes employed tens of thousands of agents to systematically spy on citizens (Gläßel and Paula 2019;Lichter, Löffler, and Siegloch 2021).…”
Section: Introductionmentioning
confidence: 99%